2021
DOI: 10.1002/jssc.202100684
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of transformation products of rocket fuel unsymmetrical dimethylhydrazine in air using solid‐phase microextraction

Abstract: Quantification of unsymmetrical dimethylhydrazine transformation products in ambient air is important for assessing the environmental impact of heavy rocket launches. There are very little data of such analyses, which is mainly caused by the low number of analytes covered by the available analytical methods and their complexity. A simple and cost‐efficient method for accurate simultaneous determination of seven unsymmetrical dimethylhydrazine transformation products in air using solid‐phase microextraction fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Overall, the studies provide valuable information for environmental monitoring and risk assessment related to rocket launches. Bukenov et al [95] studied the use of solid-phase microextraction (SPME) and gas chromatography-mass spectrometry (GC-MS) to detect and quantify transformation products of rocket fuel unsymmetrical dimethylhydrazine (UDMH) in air samples. The study identified several essential transformation products of UDMH in air, including 1,1-dimethylhydrazine, formaldehyde, and acetaldehyde.…”
Section: Research Status On Udmh Fuelmentioning
confidence: 99%
“…Overall, the studies provide valuable information for environmental monitoring and risk assessment related to rocket launches. Bukenov et al [95] studied the use of solid-phase microextraction (SPME) and gas chromatography-mass spectrometry (GC-MS) to detect and quantify transformation products of rocket fuel unsymmetrical dimethylhydrazine (UDMH) in air samples. The study identified several essential transformation products of UDMH in air, including 1,1-dimethylhydrazine, formaldehyde, and acetaldehyde.…”
Section: Research Status On Udmh Fuelmentioning
confidence: 99%